1977
DOI: 10.1002/jez.1402020107
|View full text |Cite
|
Sign up to set email alerts
|

The effects of temperature and season of collection on the onset and duration of diapause in embryos of the annual fish Nothobranchius guentheri

Abstract: Annual fish are found in temporary bodies of water in habitats of alternating rainy and dry seasons. The populations survive the dry seasons in the form of embryos encased in the bottom mud. Several genera of annual fish have been reported to exhibit diapause (developmental arrest) at three specific stages of development and it has been proposed that through this adaptation the populations are able to survive the variable durations of the dry seasons. The effects of incubation ans spawning temperatures, and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 14 publications
2
49
0
Order By: Relevance
“…A. viarius also reached somitogenesis (10 somites or less) in 16 days (Arezo et al, 2007), while A. nigrofasciatus reached this stage in about 12 days. This discrepancy could be further enhanced if the temperatures employed were the same, since the speed of development is usually directly related to the temperature (Markofsky & Matias, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…A. viarius also reached somitogenesis (10 somites or less) in 16 days (Arezo et al, 2007), while A. nigrofasciatus reached this stage in about 12 days. This discrepancy could be further enhanced if the temperatures employed were the same, since the speed of development is usually directly related to the temperature (Markofsky & Matias, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Embryos can enter a facultative developmental arrest or diapause at three distinct stages of development, which allow them to survive the variable durations of the dry seasons. Little is known about the mechanisms that trigger the onset and duration of each diapause, except that in Nothobranchius guentheri low temperature and low oxygen concentration increase the proportion of embryos entering diapauses (Peters, 1963;Markofsky and Matias, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Inglima et al (1981) and Levels et al (1986b) reported that embryonic development with its diapauses is sensitive to substances produced and released into the water by the adult fishes. Among the exogenous (environmental) factors, capable of affecting diapauses, are oxygen availability (Peters 1963, Levels et al 1986a, dehydration of the substrate (Peters 1963, Wourms 1972c, Matias 1982) and temperature (Markofsky & Matias 1977a, Matias & Markofsky 1978. Season-dependent variations in diapause frequency were also found (Markofsky & Matias 1977a).…”
Section: Introductionmentioning
confidence: 99%